Writing interactive music for video games : a composer's guide - Sweet, Michael, ....- (Upper Saddle River : Addison-Wesley, 2015)
Written by the developer of Berklee School of Music's pioneering game scoring program, this guide covers everything professional composers and music students need to know about composing interactive music for video games, and contains exclusive tools for interactive scoring—tools that were previously available only at Berklee. Drawing on twenty years of professional experience in the game industry, Michael Sweet helps you master the unique language of music storytelling in games. Next, he walks you through the entire music composition process, from initial conceptualization and creative direction through implementation. Inside, you'll find dozens of examples that illustrate adaptive compositional techniques, from small downloadable games to multimillion dollar console titles. In addition, this guide covers the business side of video game composition, sharing crucial advice about contracts, pricing, sales, and marketing.
Includes bibliographical references and index.
Keywords: Video game music -- Instruction and study